International sport management: creating an international learning and teaching community. (5th June 2008) - Danylchuk, Karen E.; Doherty, Alison; Nicholson, Matthew; Stewart, Bob
This paper provides an overview of the inception, design and delivery of an 'International Sport Management' (ISM) subject involving three partner universities in Australia, Canada and the USA. This unique international learning and teaching community has provided undergraduate sport management students and sport management academicians at geographically distant universities with an opportunity to interact and collaborate through an online learning environment, specifically through the use of a WebCT platform and case study approach. The challenges faced in delivering this subject and the ongoing changes to this unique form of learning are also presented.